Diseño y simulación de un sistema de generación fotovoltaica de tipo off-grid considerando análisis de la demanda de energía - Alvarez Agama, Andrés Sebastián (2022)
This technological proposal consisted of the design and simulation of an off/grid photovoltaic generation system considering the energy demand of block "B" of the Technical University of Cotopaxi, within the project it was possible to verify the waste of solar resources due to the lack of a photovoltaic system, so we proceeded to develop its sizing, The project started with obtaining the energy demand of 30.61 kW, the calculation of the number of solar panels was 90 panels of 385 Wp generating a power of 34.7 kW, an MPPT inverter of 45 kW was dimensioned, so it was defined a group of 15 panels connected in series and 6 in parallel, its orientation was towards the north with an angle of inclination of 15°, By means of the simulation a result report was obtained where it was mentioned that at the output of the inverter there is an efficiency ratio of 87.5% where the annual energy generated is 58.61 MWh/year while by means of the calculations 57.54 MWh/year is generated obtaining an error of 1.83 %, also the annual and monthly amount of the generation was determined, that according to the tariff schedule the cost of kWh for public entities is 0.065 USD/kWh therefore, For an annual generation of 57.53 MWh/year, an annual amount of 3814.9 USD was obtained. Finally, the generation curves of the solar panel for May 19, 2021 were obtained, in which a comparison was made with the demand curve for the same day but in the year 2022, the photovoltaic system covers part of the demand of block "B" of the University, the highest generation peak is 33 kW and the highest demand peak is 30 kW.